Heparin-Associated Thrombocytopenia Treatment with Low Molecular Weight Heparin - Vitoux, Jean-F; Mathieu, Jean-F; Roncato, Martine; Fiessinger, Jean-N; Aiach, Martine (Thrombosis and Haemostasis, 1986)
Eight patients with heparin associated thrombocytopenia (HAT) were treated by a low molecular weight heparin derivative (LMW). Biological and clinical improvement occurred in all patients. This efficiency confirms the antithrombotic activity of LMW and allows its use in patients with HAT.
Keywords: Heparin-associated thrombocytopenia; Thrombus formation; Low molecular weight heparin